Obesidade infantil como um problema de macromarketing: fatores de influência e contribuições de marketing social - Silva, Rebeca Sá do nascimento (2015)
The research studied childhood obesity as a problem of macromarketing scope, aiming to identify the contributing factors for their growth and how these factors are configured between parents and children, to understand the behavioural influences this context that are amenable to intervention social marketing for changing harmful behaviours. Thus, the study had the objective of building a theoretical framework of behavioural factors relevant to childhood obesity, configure key factors relevant to social marketing associated with parents and children, and finally, based on the relationships among the factors, analyse stocks government to support the development of effective public policies. In this sense, the theoretical framework discussed issues related to expanded marketing vision, outlining this research in a perspective of macromarketing and social marketing against a backdrop of bad food intake and prior to public health problems such as obesity. From a qualitative approach, the method used was the interview with semi-structured and in-depth itineraries, applied to the main agents of change this reality, parents of children overweight or obese with up to 12 full years. For this, 17 mothers were interviewed by audio recording and subsequently the interviews were transcribed and systematized according to categories (factors and sub-factors) pre-defined and interrelated dimensions microenvironmental and macroenvironmental the study. In the data analysis it can be seen that the lines are representative of the factors studied in the research and converging to the discussion in the applied literature, showing a growing and multi-sector scenario of childhood obesity, and subject to social marketing interventions in negative behaviours and drivers of disease. From the analysis it was possible to add four new factors of childhood obesity in this study, which emerged from the analysed reports: bullying, aggression, anxiety for food and use of medicines; these can be viewed as obesity frame consequences and in some instances, causes the increased amount of food intake. Generally, the family, the parents' role, is the major factor in the prevalence of overweight, however, these actors, parents and children, are strongly influenced the child's living environment (micro) and external and social environment (macro). That said, on the assumption that the study demonstrates a systemic and systematic way to shape the behavioural factors of influence of childhood obesity, suggests the use of social marketing expertise along with information about the real scenario of Brazilian childhood obesity to development of effective public policies and far-reaching. Thus, it is expected that the relationship between the factors and the design of how to shape the lives of those surveyed serve as government and social stimulus to behavior change through actions and interventions with a strategic and comprehensive vision. Also recommended the inclusion of social marketing stakeholders, based on Benchmark Criteria Andreasen (2002), to achieve a reduction in obesity in Brazil by promoting health effectively, educating and mobilizing the community, parents and the children.